LEGAL CULTURE OF PHARMACIST IN THE PERSPECTIVE O PHARMACEUTICAL SERVICES STANDARD IN PHARMACIES - Endang Sutrisno; Hanari Fajarini (Jurnal Dinamika Hukum, 2016)
Pharmacists are burdened with obligations as cited in Regulation of the Minister of Health, No. 35 of 2014 on the Standards of Pharmaceutical Services in Pharmacy. This paper uses socio-legal approach aiming at examining the norms associated with the protection of the patient’s safety. The applicability of the rules faces some obstacles since the legal culture of apathy still exist, so that the understanding and awareness of legal compliance is not achieved. Legal culture of apathy regarding ideas, concepts, perceptions, views, values and behaviors that are not constructive, affect the workings of law towards the observance and compliance to the law, as a result, the purpose of the law to provide justice and legal certainty to the practicians suchas pharmacists, patients and owner of the pharmacy services, are not fully able to interpret the substance of the regulation of the Minister of Health, Number 35 of 2014. As a result of this legal culture, the implementation of the Regulation of the Minister of Health No. 35 of 2014 is directed more on aspects of benefactive purpose than on the aspect of legal certainty.Keywords: pharmacists; apathy legal culture; the purpose of law.